2018
DOI: 10.1155/2018/8285653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variant rs755622 Regulates Expression of the Multiple Sclerosis Severity Modifier D-Dopachrome Tautomerase in a Sex-Specific Way

Abstract: Multiple sclerosis (MS) is a sex-specific autoimmune disease involving central nervous system. Previous studies determined that macrophage migration inhibitory factor (MIF) and its homologue D-dopachrome tautomerase (DDT) sex-specifically affect MS progression. Moreover, other studies reported that rs755622 polymorphism in promoter region of MIF gene is associated with risk of MS and affects the promoter activity to regulate MIF expression in a sex-specific way. Given that MIF and DDT share a part of promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…These results are consistent with a previous study, which reported that stress could elevate MIF levels in patients [14]. Further, these results suggest that MIF has a sex-specific effect, as was reported in a MS disease study [16, 17]. We found no difference in MIF levels between male and female patients or male and female healthy controls, but different levels of plasma MIF between the stress-induced hyperglycemia and the euglycemia groups were only found in male patients, suggesting that the pathogenetic effects of MIF in nondiabetes STEMI are sex dependent.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a previous study, which reported that stress could elevate MIF levels in patients [14]. Further, these results suggest that MIF has a sex-specific effect, as was reported in a MS disease study [16, 17]. We found no difference in MIF levels between male and female patients or male and female healthy controls, but different levels of plasma MIF between the stress-induced hyperglycemia and the euglycemia groups were only found in male patients, suggesting that the pathogenetic effects of MIF in nondiabetes STEMI are sex dependent.…”
Section: Discussionsupporting
confidence: 93%
“…It is hypothesized the inverse regulation of MIF/CD74 and CXCR4 expression in B cells in CIS patients with rapid development of CDMS may witness the existence of an immature B cell populations with senescent features, that escaped peripheral tolerance [21]. Clearly, the data of Rijvers and coworkers [21] differ from our own present analysis and the previous study indicating increased levels of MIF during CIS [20], as well as with the increasing evidence of upregulated secretion and signaling of MIF and DDT in MS and its rodent counterpart [8,9,22,23]. The reasons for these divergent findings are difficult to explain and remain to be established having in mind the possible occurrence of multiple variables, including sex and age of the patients in the different studies, along with presenting clinical characteristics, including body mass index and eventually misdiagnosed comorbidities.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies have pointed to other genetic polymorphisms that affect MS only in male patients (13,14) that could explain part of the difference in prevalence and course of MS between sexes. We observe a trend for a lower expression of CD69 in activated CD3 + cells in male patients carrying rs12959006 * T allele.…”
Section: Discussionmentioning
confidence: 99%